Analyzing Consumer Confidence Across Income Groups in the Philippines: Evidence from Consumer Expectations Survey - de Leon, Christian S (Advances in Social Sciences Research Journal, 2025)
This study examines consumer confidence in the Philippines, focusing on the relationships between key confidence indices and disparities across income groups using ten years of data from the Consumer Expectations Survey (CES), a quarterly survey conducted by the central bank to assess the confidence levels of Filipino households regarding their family’s financial situation and the overall economic condition. Results show strongly positive and statistically significant correlations between all confidence indices and highly statistically significant differences in confidence regarding family financial situation and family income across income groups. However, differences in confidence about the economic condition were not statistically significant. These findings underscore the importance of considering socio-economic status in formulating economic policies that address consumer expectations.